Screening of Blumea lacera and Cyathocline purpurea (Asteraceae) for mineral profiles, heavy Metals and phytochemicals - S.D.MANE; V.B.SHIMPALE (International Journal of Pharma and Bio Sciences, 2017)
The aim of this study was to analyze weed species for their screening for presence of essential and heavy metals and phytochemicals. Essential minerals are the metals which plays vital role in plants life cycle so they are needed for growth while heavy metals are the metals of relatively high density or of high atomic weight which causes some adverse effects also. For the extraction of heavy metals and essential minerals two weed samples were selected viz., Blumea lacera and Cyathoclinepurpurea. Both these weeds are common in occurrence and belongs to family Asteraceae. The quantitative analysis of metals from these plants has been done by using standard analytical techniques. Some metals for which these samples were analyzed are N, P, K, Ca, Mg, S, Na, Zn, Fe, Cu, Mn, Mo, B, Cd, Cr, Pb, Ni, As, Si, Hg. Atomic absorption spectrophotometer, flame photometer, UV-spectrophotometer and Kjeldhals apparatus were used for analyzing the samples. Entire plant sample was estimated to get the proportion of heavy metals in ppm or % unit. Both plant shows presence of moderate amount of all micronutrient and macronutrient. Magnesium metal shows higher concentration in Blumea lacera i.e.5.21% while in Cyathocline purpurea sulphur metal present in higher concentration i.e. 6.42%. Along with essential minerals and heavy metals, phytochemicals like tannin, flavonoid and alkaloid also analyzed quantitatively by using standard methods. Identical result is shown by using calibration curve which is obtained with the help of standard solutions.